Aerodynamic characteristics of a long-span cable-stayed bridge under construction. (1st April 2019) - Ma, Cunming; Duan, Qingsong; Li, Qiusheng; Liao, Haili; Tao, Qi
Highlights: Wind characteristics including Mean and turbulence are measured at field site. The pressure distributions on the bridge girder are obtained from field measurements. The aerodynamic admittance of the bridge girder are tested in field measurement. The bridge buffeting responses are compared between tested and FEM calculation. Abstract: Aerodynamic characteristics or parameters such as pressure distributions, static force coefficients, and aerodynamic admittance of a long-span cable-stayed bridge girder during the erection stage have been investigated through field measurements. Buffeting response of the bridge girder at the longest single-cantilever stage was estimated via the field measurements and finite element analysis. Results of this study suggest that the drag- and lift-force coefficients, estimated from the field measurements, increase with an increase in the angle of attack. The Sears function and Davenport's approximation function were found to overestimate corresponding aerodynamic admittances in the low frequency region. In the high frequency region, the Sears function tends to underestimate the lift force and moment aerodynamic admittances. Davenport's approximation function were found to be smaller compared to those drag force aerodynamic admittance obtained via the field measurements. Lastly, the buffeting response of the bridge obtained via the finite element analysis and field measurements were found to agree well within a given range of wind speed.